2021
DOI: 10.1021/acs.jpclett.1c02013
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly and Circularly Polarized Luminescence from Achiral Pyrene-Adamantane Conjugates by Selective Inclusion with Cyclodextrins

Abstract: The interaction between guest chromophores or lumiphores with host chiral cavity and their induced chirality is an important topic in supramolecular chemistry. Kodaka and Harata proposed a rule to explain the induced circular dichroism of the guest chromophores by host cyclodextrins. However, it remains unknown how a circularly polarized luminescence (CPL) signal will change when the lumiphores interacted with cyclodextrins in different modes. Here, we designed an achiral pyrene-adamantane conjugated guest mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…This enhanced excimer emission indicates the formation of a pyrene dimer in the barrel-like cavity formed by two γ-CDs. 16–18 The formation of inclusion complexes between 1-PBA/γ-CD is further confirmed by 1 H NMR (Fig. 1c).…”
Section: Resultsmentioning
confidence: 63%
“…This enhanced excimer emission indicates the formation of a pyrene dimer in the barrel-like cavity formed by two γ-CDs. 16–18 The formation of inclusion complexes between 1-PBA/γ-CD is further confirmed by 1 H NMR (Fig. 1c).…”
Section: Resultsmentioning
confidence: 63%
“…Liu et al reported selective interactions of a pyrene–adamantane dual‐site guest molecule, N ‐(pyren‐1‐yl)adamantane‐1‐carboxamide (ACNP), with α/β/γ‐cyclodextrins (Figure 2). 69 α‐Cyclodextrin hardly interacted with either site of ACNP effectively and could not induce CPL because the cavity is too small for both the pyrene and adamantane sites. In contrast, β‐cyclodextrin captured both sites, and the resulting β‐cyclodextrin−ACNP 2:1 complex displayed pyrenyl monomer CPL at 390 nm with a g lum value of −4.8 × 10 −3 ([β‐cyclodextrin] = 10 mM, [ACNP] = 0.1 mM).…”
Section: Organic Host–guest Systemsmentioning
confidence: 99%
“…The PL peak of S-BNPCN-o-CP becomes weakened gradually by increasing BN3 concentration (Fig. 3e), indicative of FRET process from S-BNPCN-o-CP to BN3 [58][59][60] . In the absence of BN3, only the CP-PL signal at ~400 nm from S-BNPCN-o-CP is observed, without other CP-PL signals.…”
Section: Resultsmentioning
confidence: 94%